“El Museo en Camino” : Confluence of discourses, processes and artistic-educational practices - Paz García, María Begoña; Martínez Barreiro, África; Gradín Carbajal, Cristian (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
"El museo en camino" is a project focused on art, education and childhood developed by an interdisciplinary group of female artists, teachers and architects. It is aimed at disseminating the artistic, cultural and social values of the Way to Santiago de Compostela and at showing the Galician heritage kept in the Museum of Pontevedra to children living in small towns and villages located along the Portuguese Way. In order to do so, an educational tool was designed – the portable museum –, which offered a visit to the museum and a workshop on plastic arts. Moreover, once the project was completed, an educational exhibition was organised.